2015
DOI: 10.1038/ncomms8238
|View full text |Cite
|
Sign up to set email alerts
|

Real-time intermembrane force measurements and imaging of lipid domain morphology during hemifusion

Abstract: Membrane fusion is the core process in membrane trafficking and is essential for cellular transport of proteins and other biomacromolecules. During protein-mediated membrane fusion, membrane proteins are often excluded from the membrane–membrane contact, indicating that local structural transformations in lipid domains play a major role. However, the rearrangements of lipid domains during fusion have not been thoroughly examined. Here using a newly developed Fluorescence Surface Forces Apparatus (FL-SFA), migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…Force is known to drive destabilization of apposed artificial lipid membranes toward fusion threshold (8). We found that the average eccentricity of the docked SVs' ellipsoid shape in resting terminals was significantly greater than that of undocked SVs.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Force is known to drive destabilization of apposed artificial lipid membranes toward fusion threshold (8). We found that the average eccentricity of the docked SVs' ellipsoid shape in resting terminals was significantly greater than that of undocked SVs.…”
Section: Discussionmentioning
confidence: 77%
“…These interactions, which produce force by forming a coiled coil called the SNARE core complex, are regulated by auxiliary proteins (1,(5)(6)(7). Such force on the VM-PM contact site may also play a role in their fusion (8). At typical synapses, docking and fusion take place at structurally specialized regions along the PM called active zones (9,10).…”
mentioning
confidence: 99%
“…At concentrations lower than the CAC, 5aTHQs behave as hydrophilic molecules in aqueous solutions,s howing low/no membrane affinity.W hen the concentration is higher than the CAC, aggregate forms appear.5 aTHQs in aggregate forms behave as hydrophobic molecules,a nd can fuse with and reside in lipid membranes.Ingeneral, the most important force leading to the direct fusion of membranes is hydrophobic interactions, which supports this model. [29] Molecules in membrane structures have to flexibly move for hemifusion by decreasing steric and electrostatic repulsions. [29] Molecules in membrane structures have to flexibly move for hemifusion by decreasing steric and electrostatic repulsions.…”
Section: Resultsmentioning
confidence: 99%
“…In the presence of calcium but absence of SNAREs, any fusion-related events are detected mainly if the integrity of the supported bilayer was partly compromised (i.e., showing defects) (17,18). The likelihood for membranes to cross the hydration barrier but not to merge increases strongly from 9 to 15% when PEG and calcium were added to the system, attributed to lowering of the hydration barrier.…”
Section: Resultsmentioning
confidence: 99%
“…Although precise data for thermodynamics and kinetics of SNARE zippering and unzippering are now available (11,14,15), few studies address how the energy landscape of membrane fusion is shaped by participation of SNAREs. Israelachvili and coworkers (16)(17)(18) were among the first to measure fusion events in the absence of proteins as a function of external force using a surface force apparatus, and Moy and coworkers (19) measured the interaction forces between reconstituted SNARE derivatives, reporting fusion events as mechanical instabilities in the approach curve of the two membrane-coated substrates. Additional advances have been made by Brouwer et al (20) and Keidel et al (21) by using optical tweezers for studying some aspects of membrane fusion.…”
mentioning
confidence: 99%